Chagosendines A – C, New Metal Complexes of Imidazole Alkaloids from the Calcareous Sponge Leucetta chagosensis. Issue 2 (30th January 2018) - An, Bang; Yin, Fuling; de Voogd, Nicole J.; Chen, Xiaoguang; Cheng, Wei; Lin, Wenhan
Abstract : Chemical examination of the bright yellow sponge Leucetta chagosensis resulted in the isolation of three new imidazole‐based alkaloid complexes namely chagosendines A – C (1  – 3 ), together with known analogues pyronaamidine, naamidine J, and naamine C. Their structures were determined on the basis of extensive spectroscopic (IR, MS, NMR, and single‐crystal X‐ray diffraction) analysis in association with the chemical conversion. The isolated alkaloids together with three synthesized new homodimer complexes were evaluated for the cytotoxic activities against a panel of tumor cell lines. The copper complexes of imidazole alkaloids2 and3, as found from nature for the first time, exerted selective and remarkable activities against the tumor cell lines K562, HepG2, and HeLa. Abstract :